Sidang Ilahi Elohim Dalam Mazmur 82:1 - Marthin Steven Lumingkewas; Firman Panjaitan (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2020)
In the Old Testament Yahweh is frequently called El. The question is raised whether Yahweh was a form of the god El from the beginning or whether they were separate deities who only became equated later. They whom uphold theory Yahweh and El were conceived as separate deities holds that Yahweh was a southern storm god from Seir and so on, which was brought by the Israelites and conflated with the Jerusalem patriarchal deity.On the other side there are scholars who hold and conceived Yahweh and El as one single deity. These scholars defend this position most commonly on the grounds that no distinction between the two can be clearly found in the Hebrew Bible. The methodology used in this paper is literary – historical and social interpretations, with the main method being the "diachronic and dialectical theology of Hegel". The simple Hegelian method is: A (thesis) versus B (anti-thesis) equals C (synthesis). The author analyzes (thesis) by collecting instruments related to ancient Semitic religions; it includes data on El and Yahweh assembly obtained from Hebrew text sources and extra-biblical manuscripts which are then processed in depth. The antithesis is to analyze El's assembly development in Israel – especially in Psalm 82. While the synthesis appears in the nuances of the El’s assembly believe in ancient Israel. The focus of this paper's research is to prove 2 things: first, is Psalm 82: 1, is an Israeli Psalm that uses the patterns and forms of the Canaanite Psalms; especially regarding religious systems that use the terminology of the divine council. Second, to prove that El and Yahweh in the context of this Psalm are two different gods, of which this view contradicts several ANET experts such as Michael S, Heisser who sets El and Yahweh in this text as identical gods. The results of this study attempt to prove that Israel and the Canaan contextually share the same religious system, and are seen to be separated in the Deuteronomist era with their Yahwistic reforms.